Simulation of the effects of electrolyte concentration on Dye Solar Cell performance - Oktiawati, U.Y. (IEEE Computer Society, 2014)
Solar energy being one of the renewable energy sources can now be harnessed by the third generation solar technology in the form of Dye Solar Cell (DSC). Although DSC can offer flexibility, low in production cost and easy to fabricate, the problem still remains with its low efficiency. Various aspects of the components of the DSC can be studied in order to improve the efficiency. As one of DSC elements, electrolyte concentration may affect the efficiency as well as the performance of DSC. Higher electrolyte concentration may increase the electron mobility as well as the efficiency of DSC. However, it may also enhance the possibility of recombination that may reduce the efficiency of DSC. In this paper, simulation of different electrolyte concentrations is conducted in order to optimize the performance of DSC. Parameters obtained from other experimental work were used as the input for the simulation program. The result is then compared and validated with other experimental work which has the closest experimental condition. Results showed that the optimum electrolyte concentration is 1.5M of iodide with efficiency of 7.5504 as the compromise for higher electron mobility and less recombination rate. Â© 2014 IEEE.